ISLAMIC THOUGHT, NATIONALISM, AND MULTICULTURALISM - Zuly Qodir (Graduate Program of Pontianak Institute of Islamic Studies, 2014)
The inclusive interpretation of religious texts will contribute to the development of plural and multicultural theological perspective rather than develop anexclusive and closed theology. There is a lot of momentum which can serve as a point of departure for developing multicultural theology in Indonesia when humanitarian issues are faced by so many believers, especially the Muslims, such as floods, earthquakes, landslides, and ignorance that continue to haunt the entire country rather than busy interfering with other people’s faith. Judging by very diverse field conditions, there is a final note regarding multiculturalism in the context of Islam in Indonesia. There are internal and external problems that affect religious understanding in this country. The internal factors are the existence of a highly diverse understanding, from moderate, progressive to conservative, thus influencing each other’s understanding of the Indonesian Muslims. The internal factor cannot be underestimated for it is perceived to be influential in the community, so it has to be an understanding that is able to push the development of multiculturalism and pluralism in Indonesia. Meanwhile the external factors should also get attention in this study. Keywords: Islam, perspective, multiculturalism, and Indonesia.